2021
DOI: 10.1016/j.stemcr.2021.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Differentiation of Adult Tissue-Derived Human Thyroid Organoids

Abstract: Total thyroidectomy as part of thyroid cancer treatment results in hypothyroidism requiring lifelong daily thyroid hormone replacement. Unbalanced hormone levels result in persistent complaints such as fatigue, constipation, and weight increase. Therefore, we aimed to investigate a patient-derived thyroid organoid model with the potential to regenerate the thyroid gland. Murine and human thyroidderived cells were cultured as organoids capable of self-renewal and which expressed proliferation and putative stem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 59 publications
2
53
3
1
Order By: Relevance
“…These three-dimensional cultures are representative in vitro model systems, which recapitulate human physiology (11). While we were finalizing the current study, Coppes and colleagues reported a first description of transplantable human (and mouse) thyroid organoids (12). In this study, we report similar findings and apply thyroid follicular cell organoids (TFCOs) to model Graves' disease using patient sera.…”
Section: Significancesupporting
confidence: 65%
See 3 more Smart Citations
“…These three-dimensional cultures are representative in vitro model systems, which recapitulate human physiology (11). While we were finalizing the current study, Coppes and colleagues reported a first description of transplantable human (and mouse) thyroid organoids (12). In this study, we report similar findings and apply thyroid follicular cell organoids (TFCOs) to model Graves' disease using patient sera.…”
Section: Significancesupporting
confidence: 65%
“…Since we observed a gradually increasing growth rate from passage 5 onwards, we hypothesized that such stem cell markers would become evident when comparing tissue to early passage TFCOs and would increase in expression from early to late passage organoids. No significant change in expression was identified in the putative stem cell markers SCA1 (17,18), ABCG2 (17,19), FUT4 (12), GATA4 (20), HNF4A (20), NANOG (21), OCT4 (12,17,(20)(21)(22), and HHEX (15,23) in human TFCOs (SI Appendix, Fig. S3 A-J).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Human embryonic stem cell (ESC)-based protocols have been developed and led to the generation of several types of human organoids that include brain, intestine, stomach, liver, kidney, lung, endometrium, prostate, pancreas, and retina 8,9 . With regard to the thyroid, murine ESC-derived organoids have been shown to recapitulate in vitro the developmental stages of the thyroid gland with the ability to produce TH in vitro and in vivo after transplantation to mice with ablated thyroid glands [11][12][13][14][15] .…”
mentioning
confidence: 99%